Adolescent/Young Adult Perspectives of a Therapeutic Music Video Intervention to Improve Resilience During Hematopoietic Stem Cell Transplant for Cancer. (4th December 2019) - Haase, Joan E; Robb, Sheri L; Burns, Debra S; Stegenga, Kristin; Cherven, Brooke; Hendricks-Ferguson, Verna; Roll, Lona; Docherty, Sharron L; Phillips, Celeste
Abstract: This empirical phenomenology study reports adolescents/young adults (AYA) experiences of the therapeutic music video (TMV) intervention arm of a randomized controlled clinical trial (Children's Oncology Group; COG-ANUR0631; R01 NR008583) during hospitalization for a hematopoietic stem cell transplant. A purposive subsample of 14 AYA were interviewed using a broad open-ended data-generating question about their TMV intervention experiences. At the end of each interview, we also asked AYA for suggestions on how to improve the TMV. Analysis of the narrative data resulted in four theme categories: (a) An Interwoven Experience of the Transplant and TMV Intervention; (b) TMV as a Guided Opportunity for Reflection, Self-Expression, and Meaning-Making; (c) Telling My Story: The Work of Deriving Meaning; and (d) A Way to Overcome the Bad Side of Cancer. AYA suggestions for improving the TMV are also summarized. Findings provide insight into ways the TMV supports AYA efforts to overcome distress and challenges by providing opportunities to reflect on what is meaningful, connect with others, and explore/identify personal strengths. Findings also inform our understanding about how the TMV may have functioned (i.e., mechanisms of action) to bring about significant change in AYA self-reported outcomes (i.e., positive coping, social support, and family function) for this trial.